EFFECTS OF HOMEWORK COMPLIANCE ON COGNITIVE‐BEHAVIORAL THERAPY WITH D‐CYCLOSERINE AUGMENTATION FOR CHILDREN WITH OBSESSIVE COMPULSIVE DISORDER. Issue 12 (15th September 2015) - Olatunji, Bunmi O.; Rosenfield, David; Monzani, Benedetta; Krebs, Georgina; Heyman, Isobel; Turner, Cynthia; Isomura, Kayoko; Mataix‐Cols, David
Abstract : Background: The present study examined the effects of homework compliance on outcome from cognitive behavioral therapy (CBT) for children with obsessive‐compulsive disorder (OCD) and the extent to which these effects differ as a function of augmentation of CBT with D‐cycloserine (DCS). Methods: Twenty‐seven youth with OCD were randomized to either 50 mg DCS or placebo (PBO) administered immediately after each of 10 CBT sessions, primarily consisting of exposure and ritual prevention (ERP). Independent evaluators assessed OCD severity using the Children's Yale–Brown Obsessive–Compulsive Scale (CY‐BOCS) at the start of each session. Compliance with between‐session ERP assignments was also assessed at the start of each session using the Patient ERP Adherence Scale (PEAS). Results: Greater homework compliance between the previous session and the current session was related to lower CY‐BOCS at the current session. However, the relation between homework compliance and CY‐BOCS varied by treatment condition. Higher homework compliance was related to lower CY‐BOCS for participants in the DCS condition, but not for participants in the PBO condition. Furthermore, participants receiving DCS were estimated to have significantly lower CY‐BOCS than those given PBO among those with the highest levels of homework compliance. Conclusions: DCS may more effectively facilitate the effects of CBT for youth with OCD when patients are compliant with prescribed homework. Theoretical and clinical implications are discussed.